Efektivitas Kombinasi Grafting Cangkang Kerang Darah (Anadara granosa) dan Minyak Ikan Lemuru (Sardinella longiceps) Terhadap Penurunan Jumlah Osteoklas Pada Proses Bone Repair - Dinda Divilia; Rima Parwati Sari; Paulus Budi Teguh (Denta Journal Kedokteran Gigi, 2015)
Background: In dentistry, complication post-extraction, disease periodontal, prosthetic surgery, pathological conditions, and trauma can cause alveolar bone loss and even lead to tooth loss. The use of hydroxyapatite derived from blood cockle shells is osteokondiction. Omega-3 in sardine oil will stimulate the healing process of damaged bone with decreasing in the number of the osteoclasts. Purpose: The aimed of this study to determine the Effectivity of Grafting Combination Blood Cockle Shell and Sardine Fish Oil to Decrease in The Numberof Osteoclasts in The Process of Bone Repair Methods: Animals used in research, as many as24 male Wistar rats, which then divided into 4 groups, namely the control group and the treatment group. The control group subdivided into two groups, normal healing and human application's paste. In the treatment group, also divided into two groups, group with blood cockle shell application and combination of blood cockle shell and sardine oil. Osteoclasts viewed using HPA on the 7th day. Results: Decrease in The Number of Osteoclasts on K- group : 2.67±1,033, P1 : 2.33±0.09, K+ : 1.5±0.09, P2 : 0.83±0.54. Because the data not homogeneous then used test Kruskal-Wallis test and Mann-Whitney. P1 with P2 have a difference significantly compared 0,048 , P2 with K- 0,026 (p<0,05). Conclusions: Combined administration of blood cockle shell (Anadara granosa) and sardine oil (Sardinella longiceps) significantly influence the amount of osteoclasts in the process of bone repair on the 7th day.